If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -7) = 8 + 3x Reorder the terms: 2(-7 + x) = 8 + 3x (-7 * 2 + x * 2) = 8 + 3x (-14 + 2x) = 8 + 3x Solving -14 + 2x = 8 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -14 + 2x + -3x = 8 + 3x + -3x Combine like terms: 2x + -3x = -1x -14 + -1x = 8 + 3x + -3x Combine like terms: 3x + -3x = 0 -14 + -1x = 8 + 0 -14 + -1x = 8 Add '14' to each side of the equation. -14 + 14 + -1x = 8 + 14 Combine like terms: -14 + 14 = 0 0 + -1x = 8 + 14 -1x = 8 + 14 Combine like terms: 8 + 14 = 22 -1x = 22 Divide each side by '-1'. x = -22 Simplifying x = -22
| -1=k-9 | | x-3/10=4x | | -3c+7=-17 | | 7n+x=3x-n | | 6n+3=-4n+7 | | x²√25/289 | | 12x-3y=-36 | | (6x-4)(4n-5)= | | -78=3j+7-8j | | 25=40+s | | 27x=28 | | 4x^2+14-210=0 | | p-3/8 | | 3x/y=6 | | X+17=151 | | (12-5i)(7i+5)= | | A+2(y+3)=y+7 | | 6f-4+2f=20 | | 6x-8+15=-9 | | -6x-3x=5(x-5)-3(7x+1) | | 3(-0.8+0.4y)+2y=0 | | (7r-4)(r+5)-(2r-1)(r+5)= | | 2(3y+7)=44 | | (3x+1)+(8x-24)= | | 0=.333x+4 | | -y^2=0 | | 14u-9u=45 | | 13=y+20 | | 3(-5+5x)-2x=11 | | t^2-2t=(t+3) | | 5+4w=-3 | | -3(w+4)=3w-30 |